Hubungan Pengetahuan, Sikap, Peran Tenaga Kesehatan, Dan Fasilitas Kesehatan Dengan Perilaku Pencegahan Penularan HIV Pada Ibu Hamil Di Puskesmas Simpang Rimba Kabupaten Bangka Selatan : The Relationship between Knowledge, Attitudes, Role of Health Workers, and Health Facilities with Behavior to Prevent HIV Transmission in Pregnant Women at Community Health Centers Simpang Rimba, South Bangka Regency - Novita (Indonesian Scholar Journal of Nursing and Midwifery Science, 2024)
Introduction: HIV examination of pregnant women is a mandatory program that must be offered to pregnant women who will conduct an examination of pregnancy or ANC (Ante Natal Care) in health facilities for early intervention in the prevention of HIV transmission. The purpose of this study is to determine the relationship between knowledge, attitudes, and the role of health workers and health facilities in the prevention of HIV transmission in pregnant women at the Simpang Rimba Health Center in 2022. Methods: This type of research is analytic descriptive research using quantitative methods with a cross-sectional approach. The sampling technique was total sampling with a sample of 65 people. Results: The results of the statistical test have a relationship between knowledge with the prevention behavior of HIV transmission in the mother (p-value = 0,001). There is a relationship between attitude with the prevention behavior of HIV transmission in pregnant women (p-value = 0,000). There is a relationship between health facilities with the prevention behavior of HIV transmission in pregnant women (p-value = 0,000). Discussion: The conclusion is that there is a relationship between knowledge, attitudes, and the role of health workers and health facilities in the prevention behavior of HIV transmission to pregnant women at the Simpang Rimba Health Center in 2022. for this research, a health worker to spread simple brochures and leaflets such as HIV/AIDS IEC in every place of activities or association of mothers in the community so that the information can lead to the desire of the mother to take the HIV test.